Paternal separation as an independent risk factor for irritable bowel syndrome in rural Chinese left-behind children: a multicenter cross-sectional study - Zhongcao Wei; Zhongcao Wei; Zhongcao Wei; Zhongcao Wei; Yu Zhang; Shaoxian Xu; Mei Tong; Xing Yang; Xin Xing; Fei Dai; Fei Dai; Fei Dai; et al. (Frontiers in Public Health, 2025)
BackgroundNo study has assessed the relationship between separation factors and irritable bowel syndrome (IBS). We assess the association between the separation factors and IBS in Chinese left-behind children (LBC).MethodsIn this school-based study, we analyzed data from eight representative primary and secondary schools to assess the association between separation factors and IBS in Chinese LBC based on the Rome IV criteria. While individual-level income data were unavailable, all analyses were adjusted for regional socioeconomic disparities (Guanzhong Basin vs. Northern Shaanxi vs. Southern Shaanxi).ResultsA total of 349 IBS and 7,355 non-IBS children were included, and the proportion of LBC was 21.13%. Univariate analysis showed statistically significant differences in separation status between IBS and non-IBS children (p < 0.05). Multivariate analysis showed that in the model adjusted for demographic variables, separation from both parents demonstrated the strongest association with IBS (OR = 2.2, p < 0.0001), and separation from father only (OR = 2.1, p < 0.0001) was significantly positively associated with IBS, but separation from mother only was not significantly associated with IBS (p > 0.05), and the same trend was observed in the subgroup analysis of sex. The relationship between age and IBS risk in LBC was nonlinear, and the risk of IBS in LBC was highest at age 8 years.ConclusionSeparation from father only was significantly positively associated with IBS. And the relationship between age and IBS risk in LBC was nonlinear.